Health education research: theory and practice (London: Oxford University Press)
Publishing original, refereed papers, Health Education Research deals with all the vital issues involved in health education and promotion worldwide - providing a valuable link between the health education research and practice communities.
Keywords: Health education-periodicals; Health education